Male-specific roles of lincRNA in C. elegans fertility - Shabtai, Reut; Tzur, Yonatan B. (Frontiers in Cell and Developmental Biology, 2023)
The testis is the mammalian tissue with the highest expression levels of long intergenic non-coding RNAs (lincRNAs). However, most in vivo models have not found significant reductions in male fertility when highly expressed lincRNA genes were removed. This suggests that certain lincRNAs may act redundantly or lack functional roles. In the genome of the nematode Caenorhabditis elegans, there is an order of magnitude fewer lincRNA genes than in mammals. This characteristic lowers the potential for redundancy, making it an ideal model to test these possibilities. We identified five highly and dynamically expressed lincRNAs in male C. elegans gonads and quantified the fertility of worm strains in which these genes were removed. In contrast to the hermaphrodites of deletion strains, which exhibited no significant reductions in broods, smaller brood sizes were observed in the progeny of males of three of the lincRNA deleted strains. This demonstrates reduced male fertility in worms with those genes removed. Interestingly, reduced brood size was statistically significant only in the last days of egg laying in two of these strains. This suggests the effect is due to early deterioration and aging of the transferred sperm. We detected a mild increase in embryonic lethality in only one of the strains, supporting the possibility that these lincRNAs do not affect fertility through critical roles in essential meiotic processes. Together our results indicate a sexually dimorphic outcome on fertility when lincRNA are removed and show that, unlike mammals, individual lincRNAs in C. elegans do play significant roles in male fertility.